2009
DOI: 10.1021/cm901987t
|View full text |Cite
|
Sign up to set email alerts
|

Optically pH and H2O2 Dual Responsive Composite Colloids through the Directed Assembly of Organic Dyes on Responsive Microgels

Abstract: A novel type of smart composite materials based on the directed assembly of organic dyes on a responsive microgel template was prepared and investigated. We have chosen Calcon, a monoazo dye, as model organic dye molecules and the copolymer microgel of poly(N-isopropylacrylamide-acrylic acid-acrylamide) [p(NIPAM-AA-AAm)] as template with the pAA segments designed for inducing pH-sensitivity and the pAAm segments designed for directing the highly ordered assembly of dye molecules. Transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 72 publications
1
26
0
Order By: Relevance
“…For example Wu and coworkers also studied pH responsive behavior of P(NIPAM-Am-AA) microgels in the same pH range under similar conditions and found that the value of R h increases with increase of pH of the medium and signicant change was noted in the pH range of 3.5-4.5 (pK a of AA is 4.2). 59 Similarly Khan et al reported pH responsive behavior of P(NIPAM-Am-VAA) microgels in aqueous medium. 17 They found that the value of R h of P(NIPAM-Am-VAA) microgel particles increases with increase in pH of the medium.…”
Section: Ph Responsive Behavior Of Acrylamide Based Microgelsmentioning
confidence: 96%
See 1 more Smart Citation
“…For example Wu and coworkers also studied pH responsive behavior of P(NIPAM-Am-AA) microgels in the same pH range under similar conditions and found that the value of R h increases with increase of pH of the medium and signicant change was noted in the pH range of 3.5-4.5 (pK a of AA is 4.2). 59 Similarly Khan et al reported pH responsive behavior of P(NIPAM-Am-VAA) microgels in aqueous medium. 17 They found that the value of R h of P(NIPAM-Am-VAA) microgel particles increases with increase in pH of the medium.…”
Section: Ph Responsive Behavior Of Acrylamide Based Microgelsmentioning
confidence: 96%
“…For example Wu et al measured hydrodynamic radius of P(NIPAM-Am) microgel particles as a function of pH ranging from 2.5 to 8.5 in aqueous medium at 22 C using dynamic light scattering measurement at scattering angle of 90 C and found that value of R h did not change with change in pH of the medium in aforementioned pH range. 59 However under very low pH (in highly acidic medium), these microgel particles may get swell due to electrostatic repulsion among positively charged amide groups of polymeric network. But highly pH responsive Am based system can be obtained by copolymerization of NIPAM and Am with any ionic monomer.…”
Section: Ph Responsive Behavior Of Acrylamide Based Microgelsmentioning
confidence: 99%
“…Apart from the aforementioned combinations of stimuli, there are reports on polymeric materials responding to other combinations of stimuli such as temperature‐ and glucose‐responsive fluorescent microgels,67 CO 2 ‐ and O 2 ‐responsive nanoaggregates of fluoro‐ and amino‐containing copolymers,68 or pH‐ and H 2 O 2 ‐dual‐responsive colloidal composites formed by direct assembly of organic dyes on PNIPAM‐ b ‐PAA‐ b ‐PAAm 69. A triblock copolymer of poly( N ‐isopropylacrylamide‐ b ‐ε‐caprolactone‐ b ‐ N , N ‐dimethylaminoethyl methacrylate) exhibited a response to temperature and CO 2 dual‐triggers 70.…”
Section: Dual‐stimuli Responsivenessmentioning
confidence: 99%
“…Examples of pH‐responsive gel network chains are weak polyelectrolytes with acidic (e.g., carboxylic groups) or basic (e.g., amino groups) functional groups. Changes in pH result in a shift of chemical equilibrium and a change of the ionization degree of the gel‐network chains . Following the changes of chemical structure and the interaction of the gel‐network chains with the environment, the gel‐network chains will undergo conformational changes, resulting in a pH‐induced volume phase transition (i.e., swelling–deswelling transition) of the GRIDS.…”
Section: Grids Based On Glucose Oxidasementioning
confidence: 99%